Estimation of serum folate and vitamin B12 levels in children with severe acute malnutrition - K., Anjana Murthy; Malladad, Ashwini; Kariyappa, Mallesh (International Journal of Contemporary Pediatrics, 2020)
Background: Severe acute malnutrition is the important health issue children affected in India. It is often associated with Iron, Vitamin B12 and Folic acid and other micronutrient deficiencies. These reports of declining trend of Iron and folic acid deficiency with implementation of national anemia control programme. Estimation of Serum Folate and Vitamin B12 levels in SAM children aged 6-60 months with anemia was the objective of the study. Methods: A hospital based observational study on 80 children admitted to nutritional rehabilitation center were suffering from severe acute malnutrition (SAM) in the age group of 6-60 months enrolled in the study during the period November 2018 to May 2019 .Data was collected using a predesigned and pretested Proforma, containing details of feeding, socio-economic and development history. Blood samples were sent for measurement of plasma vitamin B12 and serum folate levels. Statistical analysis was done using SPSS version 20.0. Results: Out of 80 children, majority were between the age group of 24-60 months and majority were boys (53.8%). Mean Vitamin B12 and folic acid levels being 384.61 and 8.95 respectively. 45% and 3.8% had vitamin B12 and folic acid deficiencies respectively. Majority of neurological changes and developmental delays were noted in B12 deficient group. Of the 36, B12 deficient children, majority had moderate anaemia (40.2%), normal total count (41.7%), 60% had neutropenia, 44.4% had lymphocytosis, majority had normocytic (30.9%) anemia. Conclusions: There was a moderate to high prevalence of vitamin B12 deficiency among malnourished children. Folate deficiency was found only in few. Efforts should be directed to prevent its deficiency in pregnant and breastfeeding women and their infants with special attention on malnourished children.B12 and folate deficiency shall be considered in all cases with SAM irrespective of blood indices. Treatment will have impact on prognosis of child.